Climate change mitigation and adaptation through optical-wireless communication networks: applications, challenges, and opportunities - Mrabet, Manel; Sliti, Maha (Frontiers in Climate, 2024)
There are a number of effects that are associated with climate change, some of which include an increase in the frequency of severe weather events, an increase in temperatures, and changes in the patterns of rainfall. The Sustainable Development Goal 13 (SDG13) established by the United Nations emphasizes the importance of reducing green house gas emissions, improving climate resilience, and mobilizing resources to effectively tackle climate change. The use of optical wireless communication (OWC) networks is a realistic approach that has the potential to improve climate resilience and sustainable development. However, in order to successfully integrate OWC with climate change mitigation activities, it is necessary to overcome a number of obstacles. In addition to economic factors, the limitations encompass a range of obstacles and intricate legal frameworks. The purpose of this article is to study the ways in which OWC can contribute to the mitigation and adaptation to climate change effects within SGD 13, with a special emphasis on the challenges and opportunities related to its implementation.